A scoping review of bereavement risk assessment measures: Implications for palliative care. (July 2015) - Sealey, Margaret; Breen, Lauren J; O'Connor, Moira; Aoun, Samar M
Background: Palliative care standards and policies recommend that bereavement support be provided to family caregivers, yet uncertainty surrounds whether support currently offered by palliative care services throughout developed countries meets caregiver needs. The public health model of bereavement support, which aligns bereavement support needs with intervention, may address this gap between policy and practice. Aim: The aim was to review the literature to identify bereavement risk assessment measures appropriate for different points in the caring and bereavement trajectories, evaluate their psychometric properties and assess feasibility for use in palliative care. Design: A scoping review was systematically undertaken following Arksey and O'Malley's methodological framework. Data sources: PsycINFO, CINAHL, PubMed and Cochrane Reviews databases, as well as grey literature including Internet searches of Google, World Health Organization, CareSearch, the Grey Literature Report and OAIster were searched. Bereavement organisations and palliative care websites, reference lists in obtained articles and grief and bereavement handbooks were also scrutinised. Results: Of 3142 records screened, 356 records yielded 70 grief measures. In all, 19 measures published between 1982 and 2014 were identified for inclusion in this review, and categorised for use with family caregivers at three points in time – before the patient's death ( n = 5), in the period following the death ( n = 10) and for screening of prolonged or complex grief ( n = 4). The majority had acceptable psychometric properties; feasibility for use in palliative care varied substantially. Conclusion: This review is an important preliminary step in improving the assessment of bereavement risk and, consequently, better bereavement outcomes for palliative care family caregivers.